Assessment of Farm Household Food Security and Consumption Indices in Nigeria - O. A, Ojeleye; O. A, Adebisi; T. O, Fadiji (Asian Journal of Agriculture and Rural Development, 2014)
This study was carried out to assess farm households’ food security and consumption indices. The study was conducted in Kaduna state, Nigeria. Data used for this study was collected from a total of 244 farm households with the use of structured questionnaire using a multistage random and purposive sampling technique. The main tools of analysis for this study include descriptive statistics and food security index. The study shows that about one third of the rural farm households sampled was food insecure and that the average farm size of the farm households was 2.05ha as food secure and insecure households cultivate 2.09ha and 1.96ha respectively. Average farm and non-farm income were $1,130.7 and $810.3 per annum respectively as household daily calorie consumed was found to exceed household daily calorie requirement. The food security indices for the food secure and insecure households were found to be 1.462 and 0.852 respectively. Large family size was found to lower available calorie intake of households. The study recommends the need for family planning education and policy frames to increase household farm size.